An aqueous two-phase system formed in single-component solution of α-ketooctanoic acid. Issue 54 (21st October 2021) - Xu, Huifang; Liang, Xin; Zhang, Yaping; Gao, Meihua; Du, Na; Hou, Wanguo
Abstract : An aqueous two-phase system can form in the single-component solution of α-ketooctanoic acid without any additives. Abstract : Aqueous two-phase systems (ATPSs), consisting of two immiscible water-rich phases, have received great attention. So far, all of ATPSs reported are formed by two water-soluble compounds in aqueous media. Herein, we report an ATPS formed in the single-component aqueous solution of α-ketooctanoic acid (KOCOOH), a weakly acidic surfactant, without any additives. Its formation originates from the coexistence of micelles and vesicles in the system, the former existing in the upper phase and the latter in the lower phase. The phase behavior and microstructures of KOCOOH in aqueous solution were determined. A concentration-driven stepwise aggregation was identified for the KOCOOH solution. With an increase in the KOCOOH concentration, vesicles, oil droplets, micelles, strip bilayers, and planar lamellar phase form successively; macroscopically, the system exhibits a homogeneous transparent single-phase, turbid dispersion, two phases, a bluish single-phase, and a colorless transparent single-phase in turn. The constantly changing ionization state of KOCOOH in aqueous solution plays an important role in the phase and aggregate structure transition. This work deepens the understanding of ATPSs, and the ATPS formed by KOCOOH may have potential applications such as in the separation and purification of biomolecules and the construction of hierarchical protocell models.